Graphical user interface in the SmartRiver system = Graficzny interfejs użytkownika w systemie SmartRiver - Szulim, Robert; Powroźnik, Piotr; Michta, Emil; Piotrowski, Krzysztof; Koropiecki, Igor (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The paper presents the concept of building a web application for the implementation of the graphical user interface in the SmartRiver system. The concept of cooperation with the data processing module from distributed measurement sensors and the presentation of information about the operation of the system on geographic maps will be discussed.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne